Exploring the Relationship between Self-Regulated Learning and Reflection in Teacher Education - Dawn C Buzza; Donna Kotsopoulos; Julie Mueller; Megan Johnston (University of Windsor, 2013)
Literature on teacher learning has shown links between being a self-regulated learner, reflecting effectively on one's own practice, and being described as an "adaptive expert". For instance, the metacognitive skills needed for effective reflection on teaching practice are seen as critically important to developing adaptive expertise in the context of the highly complex classroom environment. Similarly, self-regulated learning is often defined, at least in part, in terms of using metacognitive skill to adapt one's approach to complex learning situations or problems. Although there is rich literature on reflective practice in teacher education, less is known about measuring teachers' self-regulated learning or the relationship between self-regulated learning and teacher reflections. This research examines reflective practice and self-regulated learning through pre-service teachers' written reflections. The study makes a novel adaptation of a rubric designed to evaluate teacher education candidates' reflections to measure self-regulated learning. Findings suggest that the rubric could also be useful in understanding the self-regulated practices of teacher education candidates.